2013
DOI: 10.1200/jco.2013.31.15_suppl.lba9008
|View full text |Cite
|
Sign up to set email alerts
|

OPTiM: A randomized phase III trial of talimogene laherparepvec (T-VEC) versus subcutaneous (SC) granulocyte-macrophage colony-stimulating factor (GM-CSF) for the treatment (tx) of unresected stage IIIB/C and IV melanoma.

Abstract: LBA9008 The full, final text of this abstract will be available at abstract.asco.org at 7:30 AM (EDT) on Saturday, June, 1, 2013, and in the Annual Meeting Proceedings online supplement to the June 20, 2013, issue of Journal of Clinical Oncology. Onsite at the Meeting, this abstract will be printed in the Saturday edition of ASCO Daily News.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 0 publications
0
55
0
Order By: Relevance
“…5 The most successful oncolytic virus to date, talimogene laherparepvec (T-Vec), an oncolytic granulocyte-macrophage colony-stimulating factor (GM-CSF) producing herpes virus, was recently shown in a randomized phase 3 clinical trial to have a better durable response rate and a trend toward better overall survival compared to GM-CSF for unresectable melanoma. 6 There have also been encouraging results with the use of replicating vaccinia virus (VV) (New York City Board of Health Strain) expressing GM-CSF in patients with hepatocellular carcinoma where intralesional Pexa-Vec therapy (Sillajen) resulted in a 15% response rate (mRECIST) and prolongation of survival when high dose was compared to low-dose treatment. [7][8][9] VV has many potential advantages over other oncolytic viral backbones.…”
Section: Introductionmentioning
confidence: 99%
“…5 The most successful oncolytic virus to date, talimogene laherparepvec (T-Vec), an oncolytic granulocyte-macrophage colony-stimulating factor (GM-CSF) producing herpes virus, was recently shown in a randomized phase 3 clinical trial to have a better durable response rate and a trend toward better overall survival compared to GM-CSF for unresectable melanoma. 6 There have also been encouraging results with the use of replicating vaccinia virus (VV) (New York City Board of Health Strain) expressing GM-CSF in patients with hepatocellular carcinoma where intralesional Pexa-Vec therapy (Sillajen) resulted in a 15% response rate (mRECIST) and prolongation of survival when high dose was compared to low-dose treatment. [7][8][9] VV has many potential advantages over other oncolytic viral backbones.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent phase III clinical trial, an oncolytic herpes simplex virus armed with granulocyte-macrophage colony-stimulating factor (T-VEC) showed superior durable response rates in advanced melanoma patients compared with subcutaneous administration of the recombinant granulocyte-macrophage colony-stimulating factor protein. 4 An oncolytic vaccinia virus expressing the same transgene (Pexa-Vec) has shown promising results in phase II clinical trials for hepatocellular carcinoma. 5 In this case, intratumoral administration of the virus led to an increase in serum concentrations of granulocyte-macrophage colony-stimulating factor and elevation of neutrophil counts in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…was made. 13 Further logical arguments for IT delivery included the lack of a viral dilution that would occur as a result of i.v. delivery; clinical experience revealed that IT delivery was not technically difficult and was readily achievable.…”
Section: Debatementioning
confidence: 99%